\(2.\left(3+1\right).\left(3^2+1\right).\left(3^4+1\right)\)
= \(\left(6+2\right)\left(3^2+1\right)\left(3^4+1\right)\)
= \(\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)\)
= \(\left(3^4-1\right)\left(3^4+1\right)\)
= \(3^8-1\)
Chúc bạn học tốt !!!
\(2\left(3+1\right)\left(3^2+1\right)\left(3^4+1\right)\)
\(=\left(3-1\right)\left(3+1\right)\left(3^2+1\right)\left(3^4+1\right)\)
\(=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)\)
\(=\left(3^4-1\right)\left(3^4+1\right)\)
\(=3^8-1\)
=
=
=
=
Chúc bạn học tốt !!